An achievement as one of many factors of students’motivations during higher education - Коломієць, Богдан Сергійович (ScienceRise: Pedagogical Education, 2016)
Analyzing the problems of self-education at the modern stage, it became possible to diminish the number of factors that influence students’ motivation. There was defined interdependence between the notion “achievement” and communicative possibilities of teacher, necessary for presentation of correspondent information. There is a possibility to raise the internal motivation of students by presentation of the certain possible profit that will be achieved in the process of learning. Self-education is carried out by teachers or tutors who have to learn during whole the life because of continuously growing amount of information for successful exams passage by students. There was elucidated the process of transforming information into knowledge and the value of knowledge as one of sources of gaining profit